Explaining Post-Adoption Mobile Banking Usage in Indonesia Using an Integrated Technology Acceptance Model and IS Success Model: Evidence from PLS-SEM - Rr. Tri Istining Wardani; Endang Siti Astuti; Sunarti Sunarti; Mohammad Iqbal (International Journal of Environment, Engineering and Education, 2026)
Mobile banking has become a primary channel for retail financial services in emerging economies; however, prior research has focused predominantly on initial adoption intention rather than post-adoption usage behavior. This study addresses that gap by integrating the Technology Acceptance Model and the DeLone and McLean IS Success Model to explain post-adoption mobile banking usage in Indonesia. A quantitative cross-sectional survey was conducted with 544 active users of mobile banking applications from four Indonesian state-owned banks, and the data were analyzed using PLS-SEM. The results indicate that perceived ease of use significantly enhances perceived usefulness (β = 0.549, t = 14.213, p < 0.001). In turn, perceived usefulness (β = 0.192, p < 0.001), system quality (β = 0.247, p < 0.001), information quality (β = 0.225, p = 0.001), and service quality (β = 0.195, p < 0.001) positively affect user satisfaction. User satisfaction, in turn, emerges as the strongest direct predictor of self-reported actual usage (β = 0.523, t = 12.044, p < 0.001). The model explains 30.2% of the variance in perceived usefulness, 51.2% of the variance in user satisfaction, and 27.3% of the variance in actual usage. These findings indicate that post-adoption mobile banking usage is shaped not only by cognitive acceptance beliefs but also by users’ evaluations of system performance, information quality, and service support. This study contributes to post-adoption digital banking research by demonstrating that satisfaction is the central evaluative mechanism linking acceptance beliefs and service-quality perceptions to sustained behavioral usage.